The effects of trait social anxiety on affective and behavioral reactions to others' resource allocations. (1st July 2021) - Anderl, Christine; Dorrough, Angela R.; Rohrbeck, Mariví; Glöckner, Andreas
Abstract: Most studies investigating interindividual differences in the context of social decision making have focused on the decision maker. Considerably less empirical attention has been paid to interindividual differences in how recipients react both affectively and behaviorally. In two preregistered studies (total N  = 667), we examined whether heightened levels of trait social anxiety are associated with higher levels of forecasted and experienced negative affective reactions in response to uneven resource allocations by an interaction partner in a dictator game and an ultimatum game as well as corresponding hypothetical and actual behavioral reactions. In accordance with our predictions, social anxiety levels correlated with negative affective reactions; these correlations were stronger the more unevenly the resources were allocated by the other individual. The observed effects remained robust when controlling for expectations and basic personality traits and across two different economic social decision‐making tasks. This suggests that social anxiety level is an important contributor to interpersonal differences in affective reactions to another individual's uneven resource allocations.